Increasing the Added Value of Moringa Leaf into Processed Food Products by Family Welfare Movement (PKK) Merta Nadi Banjar Lantagidung, Gianyar, Bali - Ni Luh Putu Putri, Setianingsih; Semariyani, A.A. Made; Sudiarta, I Wayan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Br. Lantangidung most of the people's livelihood as farmers and silver craftsmen. Some residents grow Moringa plants for their daily food consumption. The processing of food products during the pandemic is growing rapidly, resulting in increasingly diverse and widespread processed products on the market. To empower rural communities through increasing knowledge, attitudes, skills, and behavior, it is necessary to have activities and mentoring programs that are in accordance with the needs of the community. This community service activity was carried out by PKK Merta Nadi Br. Lantangidung, Sukawati District, Bali Province. Moringa leaves are an untapped commodity in Br. Lantangidung is a processed food product. The processing of Moringa leaves into various products such as chips and Moringa leaf noodles have been produced and marketed by PKK, but marketing is still limited around Banjar. PKK women do not yet have adequate entrepreneurial, production management, and marketing skills. The solution to overcome partner problems is to provide the right technology for processing Moringa leaf chips and noodles, equipment assistance, knowledge of product packaging and labeling, and marketing. The implementation of community service activities has been running smoothly. The number of participants who took part in this activity was 10 people. Based on the evaluation results, this group mastered the technology of making chips and Moringa leaf noodles to reach 100%. Further assistance is needed for the group so that the resulting Moringa leaf chips and noodle products are of higher quality, have a longer shelf life, and have a wider marketing